Event MICE Sebagai Daya Tarik Pengunjung - Ramon Hurdawaty; Pusphanjali Pusphanjali (Journal of Tourism and Creativity, 2022)
Tourism events are planning and marketing activities that are used as communication media to introduce regional potentials such as tourist destinations and their culture with the aim of attracting tourists. Such as the event held in Bandung with the theme "Bandung Investment, Agriculture, Tourism & Trade Expo (BITTRA 2021)" by PT Visi Sinergi Antarnusa. Where this event can expand marketing networks and improve the quality of regional products in Indonesia. Indonesia sees anticipating free trade, especially in the fields of investment, tourism and trade. This research aims to determine the attractiveness, perceptions of tourists, and the role of the event. The researchers used a descriptive research method with a qualitative approach. The sampling technique used purposive sampling. Collecting data through interviews with resource persons, direct observation of the event, and documentation.The results of this study state that the MICE industry can be a tourist attraction and can help the regional economy.